Utility of the CPS + EG staging system in hormone receptor-positive, human epidermal growth factor receptor 2-negative breast cancer treated with neoadjuvant chemotherapy. (January 2016) - Marmé, Frederik; Lederer, Bianca; Blohmer, Jens-Uwe; Costa, Serban Dan; Denkert, Carsten; Eidtmann, Holger; Gerber, Bernd; Hanusch, Claus; Hilfrich, Jörn; Huober, Jens; Jackisch, Christian; Kümmel, Sherko; et al.
Abstract: Background: Pathologic complete response after neoadjuvant chemotherapy (NACT) correlates with overall survival (OS) in primary breast cancer. A recently described staging system based on pre-treatment clinical stage (CS), final pathological stage (PS), estrogen receptor (ER) status and nuclear grade (NG) leads to a refined estimation of prognosis in unselected patients. Its performance in luminal type breast cancers has not been determined. This study investigates the clinical utility of this CPS + EG score when restricted to hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2–) patients and compares the results to a cohort of unselected patients. Methods: The CPS + EG score was calculated for 6637 unselected patients and 2454 patients with HR + /HER2− tumours who received anthracycline/taxane-based NACT within 8 prospective German trials. Results: Five-year disease-free survival (DFS) and OS were 75.6% and 84.1% for the unselected cohort and 80.6% and 87.8% for the HR + /HER2− subgroup, respectively. The CPS + EG system distinguished different prognostic groups with 5-year DFS ranging from 0% to 91%. The CPS + EG system leads to an improved categorisation of patients by outcome compared to CS, PS, ER or NG alone. When applying the CPS + EG score to the HR + /HER2− subgroup, a shift to lower scores was observed compared to the overall population, but 5-year DFS and OS for the individual scores were identical to that observed in the overall population. Conclusions: In HR + /HER2− patients, the CPS + EG staging system retains its ability to facilitate a refined stratification of patients according to outcome. It can help to select candidates for post-neoadjuvant clinical trials in luminal breast cancer. Highlights: CPS + EG score predicts prognosis after neoadjuvant chemotherapy beyond pathologic complete response. We provide the largest independent validation of the CPS + EG staging system. Hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2–) subtype-specific performance is consistent with unselected patients. CPS + EG improves the stratification of patients by outcome in HR + /HER2− patients. CPS + EG helps to select HR + patients for post-neoadjuvant trials.